2019
DOI: 10.3390/v11050446
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Characterization of the Palyam Serogroup Orbiviruses

Abstract: The Palyam serogroup orbiviruses are associated with abortion and teratogenesis in cattle and other ruminants. Of the 13 different serotypes that have been identified, the full genome sequence of only one, Kasba, has been published. We undertook to perform Next Generation Sequencing (NGS) and phylogenetic analysis on 12 Palyam serotypes plus field isolates of the African serotypes in our possession. The Palyam serogroup was found to be most closely related to the African horse sickness virus group and showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Interestingly, Tracambé virus (TRV), a serotype of the sand fly-borne CGLV serogroup, was isolated from mosquitoes of the genus Anopheles (Reoviridae.org). Some serotypes of C/SBOV have been isolated from both mosquitoes and biting midges: Eubenangee virus (EUBV) [1,94], Palyam virus (PALV) [1,95], Warrego virus WARV [1], Wongorr virus (WGRV) [1], and Tibet orbivirus (TIBOV) [48]. The associations between some viruses and more than one vector family could be the result of "species jumps" permitted by fast evolution characteristic of RNA segmented viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tracambé virus (TRV), a serotype of the sand fly-borne CGLV serogroup, was isolated from mosquitoes of the genus Anopheles (Reoviridae.org). Some serotypes of C/SBOV have been isolated from both mosquitoes and biting midges: Eubenangee virus (EUBV) [1,94], Palyam virus (PALV) [1,95], Warrego virus WARV [1], Wongorr virus (WGRV) [1], and Tibet orbivirus (TIBOV) [48]. The associations between some viruses and more than one vector family could be the result of "species jumps" permitted by fast evolution characteristic of RNA segmented viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the %nt identity between Cypriot isolates (99.92-99.95%) was only slightly greater than the %nt identity between Cypriot isolates and their closest relative (ISR2008/13), 98.42-98.45%, the split network constructed here provided an accurate representation of strains originating from separate outbreaks. Although the phylogenetic network is not as common as a tree to display the evolutionary relationship between taxa, it was successfully used for tracing human-to-human transmission during the 2013-2015 Ebola epidemic in Sierra Leone [47], for supporting the field epidemiological investigation during the highly pathogenic avian influenza outbreak in British Columbia [48] or for displaying the geographical relationship amongst the serotypes of the Palyam serogroup of the Orbivirus genus [49]. In the absence of other investigative techniques such as meteorological modelling, the use of phylogenetic networks can be used to determine the origins of BTV strains.…”
Section: Discussionmentioning
confidence: 99%
“…2c) genes. In all trees, PALV 279-NA-2018 grouped within the Afrotropical clade according to its geographic origin [12]. Growth analyses in C6/36 cells showed the induction of a CPE at four dpi and high genome copy numbers of almost 10 11 copies ml −1 at six dpi (Fig.…”
Section: Phylogenetic Relationship Of Detected Orbivirusesmentioning
confidence: 91%
“…It was first isolated from Culex vishnui mosquitoes in India in 1956 [11]. So far, 13 distinct PALV serotypes have been identified that largely group according to their geographic origin in phylogenetic analyses [12].…”
Section: Introductionmentioning
confidence: 99%